2017
DOI: 10.1590/0102-311x00197915
|View full text |Cite
|
Sign up to set email alerts
|

Carga do diabetes mellitus tipo 2 no Brasil

Abstract: Type 2 diabetes mellitus currently ranks high among indicators used in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
60

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 22 publications
2
25
1
60
Order By: Relevance
“…It is mentioned that, since the regulation of the Unified Health System (UHS), the interior of the country and regions with lower socioeconomic development present difficulties for its implementation, 24 such as the North and Northeast regions. This fact is explained mainly due to the physical organizational precariousness and insufficient human and monetary resources observed in municipalities with small population contingent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mentioned that, since the regulation of the Unified Health System (UHS), the interior of the country and regions with lower socioeconomic development present difficulties for its implementation, 24 such as the North and Northeast regions. This fact is explained mainly due to the physical organizational precariousness and insufficient human and monetary resources observed in municipalities with small population contingent.…”
Section: Resultsmentioning
confidence: 99%
“…This fact is explained mainly due to the physical organizational precariousness and insufficient human and monetary resources observed in municipalities with small population contingent. 24 Deaths in hospitals are configured as a variable to evaluate the patient care process as to the outcome. 20 It is also emphasized that hospitalizations with deaths are more expensive even when they have the same average length of stay without hospitalizations.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Mexico also showed that DM was the leading cause of premature death, being higher in men than in women (20) . Another national study conducted over a 12-month period showed that chronic complications of type 2 DM accounted for 80% of PYLL (21) .…”
Section: Discussionmentioning
confidence: 99%
“…O diabetes mellitus (DM) é uma doença crônica não transmissível, considerada um grave problema de saúde pública devido à sua morbidade e mortalidade, com impactos econômicos e sociais para o país 1 . Este agravo pode ocorrer devido à produção insuficiente do hormônio insulina ou quando o organismo não é capaz de utilizar adequadamente a que produz, gerando um quadro de hiperglicemia, com consequências para a saúde como um todo 2 .…”
Section: Introductionunclassified